Implementing Publicly Funded Psychotherapy Services: What Can Ontario Learn from England? - Dane Mauer-Vakil; Katherine Lee; Joel Dissanayake; Heather Bullock (Health Reform Observer - Observatoire des Réformes de Santé, 2025)
To address high rates of unmet need for mental health services in Ontario and England, both jurisdictions undertook the implementation of publicly funded psychotherapy programs with similar objectives, albeit in different time periods. Given the policy decision in Ontario to implement this approach, this paper aims to understand the lessons Ontario can learn from England in scaling up the Improving Access to Psychological Therapy program through an application of Kingdon’s Multiple Streams Framework. The key policy difference between the two jurisdictions is that England has fully implemented its program nationwide, while Ontario is at the demonstration project phase. Therefore, a comparative health reform analysis (CHRA) is undertaken to trace the evolution of the mental health system reforms in relation to publicly funded psychotherapy services in the two jurisdictions. Across the problem, policy and politics streams, key concepts included indicator tracking, coalition building, and policy entrepreneurship. Key lessons Ontario can learn from the England story include further framing of the policy issue to rally public support and continuing to engage policy entrepreneurs in coalition building exercises. Research results may be useful for policymakers, provide groundwork for researchers, and encourage the public to play an active role in this important cause.